(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2022)
Ornithology is a division of zoology which is concerned with the scientific studies of bird. Ornithologists study the morphology, anatomy, habitat, behavior, taxonomy, systematics, evolution, eating and breeding habits of birds. Birds are often the victims of heinous crimes and aircraft accidents. Forensic ornithology is a branch of ornithology, which deals with the identification of the specific bird species from the fragmentary remains at the site of incident. Forensic Ornithologists use physical microscopic and DNA bar-coding techniques for comparing the fragmentary remains and identification. Identification of the species of the bird helps to understand their true nature, their habitat, and thus manifest how they can be conserved and protected from crimes. A bird strike can cause significant damage to an aircraft and thus to human life. The data on birds provided by forensic ornithologists can also be used to stop them from coming to airports and avoid accidents. The purpose of this review article is to promote the importance of birds and also the field and scientific techniques of forensic ornithology and enlighten people about the same. Birds help to support the climate by going about as hunters, pollinators, scroungers, seed dispersers, seed hunters, and biological system engineers. This makes them of decisive and crucial importance to humans as well as our planet. The right application of forensic ornithology can lead to safer travels both of humans and birds.